2022
DOI: 10.1111/jonm.13635
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of events of violence or aggression against nurses in the workplace: A scoping review

Abstract: Aim To identify predictors and consequences of violence or aggression events against nurses and nursing students in different work contexts. Background Workplace violence against nurses and nursing students is a very common and widespread phenomenon. Actions to manage or prevent violent events could be implemented knowing the risk factors and consequences. However, there is a lack of systematic reviews that summarize knowledge on the predictors and consequences of workplace violence. Evaluation A scoping revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 140 publications
2
19
0
Order By: Relevance
“…A review of assaults revealed factors such as a history of homelessness, incarceration, drug dependency, and psychiatric disorders with multiple ED visits and a history of aggressive behavior. Assaults occurred by patients who interacted with nurses and providers who had less than 2 years of experience, which is in line with previous research 16,26. The predominant situational trigger for violence was the patient not wanting to be discharged.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…A review of assaults revealed factors such as a history of homelessness, incarceration, drug dependency, and psychiatric disorders with multiple ED visits and a history of aggressive behavior. Assaults occurred by patients who interacted with nurses and providers who had less than 2 years of experience, which is in line with previous research 16,26. The predominant situational trigger for violence was the patient not wanting to be discharged.…”
Section: Discussionsupporting
confidence: 88%
“…Assaults occurred by patients who interacted with nurses and providers who had less than 2 years of experience, which is in line with previous research. 16,26 The predominant situational trigger for violence was the patient not wanting to be discharged. High levels of pain were noted in patients with assaultive events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to adopting the widely used Population, Concept and Context (PCC) framework proposed by the Joanna Briggs Institute (JBI) (Peters et al, 2020), the research questions were formulated using the PEO approach (Table 1), considering the Population (types of participants), Exposure of interest (independent variable (elder abuse)) and Outcome (dependent variable (safeguarding)) components. Pagnucci et al (2022) and Bettany-Saltikov (2010) recommend the PEO framework as suitable for qualitative research questions. An a priori protocol was developed, although not published.…”
Section: Stage 1-identifying the Research Questionmentioning
confidence: 99%